Quantum aspects of beam physics : the Joint 28th ICFA Advanced Beam Dynamics and Advanced & Novel Accelerators Workshop, Hiroshima, Japan, 7-11 January 2003 - Chen, Pisin, 1950-; Reil, Kevin (World Scientific, 2004)
This proceedings volume of the 3rd International Workshop on Quantum Aspects of Beam Physics, presents the latest advances in beam dynamics. The frontiers of beam research point to increasingly high energy, greater brightness and lower emittance beams with ever-increasing particle species. These demands have triggered a rapidly growing number of beam phenomena that involve quantum effects. In addition to the more established topics, this volume covers topics on high energy-density particle and photon beams for laboratory astrophysics investigations, as well as the application of beam physics e.